Combined genetic screening and traditional newborn screening to improve the screening efficiency of congenital hypothyroidism - Ye, Liang; Yin, Yifan; Chen, Min; Gong, Nian; Peng, Yong; Liu, Hao; Miao, Jingkun (Frontiers in Pediatrics, 2023)
Abstract Background Congenital hypothyroidism (CH) is an neonatal endocrine disorder. Traditional newborn screening is the mainstream method of CH screening, so as to ensure the early detection and treatment of CH. This method is limited as it has high rates of false positives and negatives. Genetic screening can be used to address the shortcomings of traditional NBS; however, the comprehensive clinical value of genetic screening is yet to be systematically studied. Methods A total of 3158 newborns who accepted the newborn screening and genetic screening were recruited for this study. Biochemical screening and genetic screening were performed at the same time. The level of TSH with the DBS was detected by time-resolved immunofluorescence assay. High-throughput sequencing technology based on targeted gene capture was used for genetic screening. The suspected neonatal was recalled and tested serum TSH, and FT4. Finally, the effectiveness of traditional NBS and combined screening was compared. Results In this study, 16 cases were diagnosed by traditional NBS. 10 cases of DUOX2mutation were found in newborn CH-related genetic screening, including 5 homozygous and 5 compound heterozygous variations. We found that the c.1588A>T mutations inDUOX2 constituting the predominant site in the present cohort. Compared with NBS and genetic screening, the sensitivity of combined screening increased by 11.1% and 55.6%, respectively. Compared with NBS and genetic screening, the negative predictive value of combined screening increased by 0.1% and 0.4%, respectively. Conclusions Combined traditional NBS and genetic screening reduces the false negative rate of CH screening and improves the early and accurate identification of neonates with CH. Our research explains the mutation spectrum of CH in this region, and provisionally demonstrates the necessity, feasibility and significance of genetic screening in newborns and provides a solid basis for future clinical developments.